The Test in the 6th Grade in a Distorting Mirror? - Dąbrowski, Mirosław (INSTED: Interdisciplinary Studies in Education & Society, 2015)
For over ten years an important element ?regulating? the functioning of our school are external examinations. Every year, hundreds of thousands of students take them at three levels, namely the test in the 6th grade, the examination of the lower secondary school and the A-level exams. Examination commissions collect an enormous amount of information about what the students can and what they have problems with. What useful information goes from these data to the educational decision-makers and to the educational system? It is difficult to say, as there are no such analyses available. In the articles I looked closer at subsequent tests in the 6th grade through the prism of the text task with highest scoring and the distribution of its effects. The conclusions, which come from this analysis, which is very easy statistically, should induce a deeper reflection on the effects of the ?regulation? mentioned above.